Institutional characteristics of education systems and inequalities—Introduction I. (December 2020) - Gross, Christiane; Hadjar, Andreas
This is the introduction into the first of multiple themed issues of International Journal of Comparative Sociology (IJCS) that are dedicated to the role of education systems as institutional settings on the reproduction of inequalities. While Introduction I presents the research program, outlines a conceptual background and discusses methodological challenges in the study of how education systems shape inequalities, introductions to the successive themed issues will deal with the current state-of-research and finally with research desiderata in terms of an outlook. The contributions will be presented at the end of each introduction. The contributions of this themed issue focus on the role of country characteristics during early childhood and the role of shadow education on educational inequalities.